THE CASE FOR EXAMINATION OF DIFFERENT METHODS USED IN LIFE SCIENCES AND SOCIAL STUDIES COURSES - Ütkür, Nur (International Online Journal of Education and Teaching, 2019)
In this study aimed to identify preservice gifted education teachers’ opinions on the instruction of life sciences and social studies courses and examine the activities, they developed regarding the several methods and techniques related to the courses. In this study, which has qualitative research features, an open-ended questionnaire was used as a data collection tool. It has been determined that the majority of preservice teachers prefer to use the constructivist approach in life sciences and social studies courses in terms of the obtained data. In addition, preservice teachers have stated drama, case study, and empathy among the methods and techniques that can be used in life sciences and social studies courses. It has been determined that preservice teachers also state various types of activities that can be used in the classroom for these methods and techniques. These types of activities include impersonations, activities which involve examples from everyday life and activities based on human relations. Keywords: life sciences and social studies course, gifted education preservice teachers, methods and techniques.